Advocating for Transgender Immigrants in Detention Centers: Cisnormativity as a Tool for Racialized Social Control. (November 2022) - Kurdyla, Victoria
Despite public concern over immigration enforcement, little attention has been given to transgender immigrants, who are disproportionately at risk for arrest and deportation. Organizations dedicated to protecting LGBT people's rights and immigrant rights have been working to address this issue and shape policy decisions to better protect transgender immigrants in detention centers; however, research has not investigated how these organizations frame transgender immigrant detainees and their experience in detention to accomplish their goals. This current study uses a content analysis of public documents spanning 2009–2021 from the American Civil Liberties Union (ACLU) and the Transgender Law Center (TLC) to investigate how two legal advocacy organizations frame the issue of transgender immigrants within detention centers. The ACLU rarely discusses transgender immigrants and thus upholds cisnormativity. When they do discuss transgender immigrants, their transgender identity is referenced as a singular issue in isolation from other facets of their identity. The TLC, on the other hand, frames immigration detention for transgender immigrants as part of a larger web of oppression. Through a comparison of the ACLU and TLC, this study underscores the role of cisnormativity as a tool for racialized social control. Findings highlight the importance of a critical, intersectional approach to immigration advocacy and scholarship that challenges the cisnormative assumptions guiding the current immigration system. Implications for future research and service provision are discussed.